OPTIMALISASI MANAJEMEN PERKANTORAN DIGITAL DALAM ADMINISTRASI LEMBAGA PENDIDIKAN ISLAM - Arief Muhammad Nurhasan; Asep Syaiful Syahbana (Eduvis : Jurnal Manajemen Pendidikan Islam, 2024)
The accelerating pace of digital transformation has fundamentally reshaped organizational administration across sectors, including Islamic educational institutions in Indonesia. Despite widespread discourse on digitalization, the specific application of digital office management within Islamic educational administration remains understudied, particularly in terms of its optimization strategies and contextual alignment with Islamic organizational values. This study aims to analyze the conceptual framework of digital office management, identify key optimization strategies applicable to Islamic educational institutions, and examine the implications of digital administrative systems for organizational effectiveness in Islamic education. A qualitative library research methodology was employed, drawing systematically on reputable academic journals, textbooks, and policy documents published within the last five years. Data were analyzed using content analysis techniques to identify patterns and propositions relevant to the research objectives. The findings reveal that optimized digital office management encompassing electronic document systems, integrated information platforms, digital communication protocols, and data-driven decision-making significantly enhances administrative efficiency, transparency, and accountability in Islamic educational institutions. The integration of Islamic organizational values within digital management systems is found to be essential for sustainable optimization.